An overview of the running performance of athletes with lower-limb amputation at the Paralympic Games 2004-2012 - Hassani, H.; Ghodsi, M.; Shadi, M.; Noroozi, S.; Dyer, B. (Sports, 2015)
This paper analyses the performances of lower-limb amputees in the 100, 200 and 400 m running events from the 2004, 2008 and 2012 Paralympic Games. In this paper, four hypotheses are pursued. In the first, it investigates whether the running performance of lower-limb amputees over three consecutive Paralympic Games has changed. In the second, it asks whether a bi-lateral amputee has a competitive advantage over a uni-lateral amputee. In the third, the effect of blade classification has been considered and we attempt to see whether amputees in various classifications have different level of performance. Finally, it is considered whether the final round of competition obtains different levels of performance in comparison to the qualification heats. Based on the outcomes of these investigations, it is proposed that future amputee-based running events should be undertaken with separate and not combined events for the T42, T43 and T44 classifications at the Paralympic Games.